Soil Microbial Seasonal Community Dynamics in Response to Cover Crop and Phosphorus Fertilizer Usage in a No-Till Corn-Soybean System in 2018 - C. L. Stewart; L. M. Starr; N. O. Nelson; K. L. Roozeboom; G. J. Kluitenberg; D. R. Presley; P. J. Tomlinson (Kansas Agricultural Experiment Station Research Reports, 2020)
This study examined microorganism community composition in plots managed with and without cover crops and three contrasting phosphorous (P) fertilizer management techniques in a no-till corn-soybean system. This work was performed in the spring and fall of 2018 at the Kansas Agricultural Watershed Field Laboratory (KAW), Manhattan, KS. The study design was a 2 × 3 complete block factorial design with three replications, with cover crop presence or absence and three levels of P fertilizer management (control, fall broadcast, and spring injected). To examine microorganism community composition, phospholipid fatty acid (PLFA) analysis was used. Only the main effect of cover crop was found to have a significant impact. Results show greater microbial biomass within plots that had a cover crop as compared to those that did not. The community structure between cover crop plots and non-cover crop plots was similar; however, their abundance was less in non-cover crop plots than in those that had a cover crop.
Keywords: no-till; cover crops; soil health; microorganisms; PLFA; phospholipid fatty acid